Integrating Multiple Micronutrient Supplementation into Antenatal Care in Rural Indonesia - Rosdiana Syakur; Ajeng Kurniati; Andi Maryam; Sutiyono (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
The This study evaluated the effectiveness of Multiple Micronutrient Supplementation (MMS) compared to Iron–Folic Acid (IFA) in improving maternal nutritional out comes in Indonesia. Maternal undernutrition and anemia contribute to low birth weight and stunting, while antenatal programs largely rely on IFA. This quasi-experimental pre–post parallel-group study was conducted in 2025 in Grobogan District, Central Java, who involved 60 pregnant women who were randomly assigned to MMS (n = 30) or IFA (n = 30). Maternal nutritional status was assessed through changes in body weight, mid-upper arm circumference (MUAC), and hemoglobin levels. Ethical approval was obtained (No. 48/Kom.etik/VI/2025). Data were analyzed using paired t-tests or Wilcoxon tests for within-group comparisons and independent t-tests or Mann–Whitney tests for between-group differences. Both groups showed significant weight gain (MMS: +2.93 kg; IFA: +3.47 kg; p < 0.05), with no significant difference between groups (p = 0.363). MUAC increased significantly in the IFA group (+0.96 cm; p = 0.018) but not in the MMS group. Hemoglobin increased significantly in the IFA group (+1.02 g/dL; p = 0.008), whereas MMS showed a non-significant decline. These findings indicate that although both supplements improved maternal weight, IFA was more effective in increasing hemoglobin.